Expression of Astragalus membranaceus phenylalanine ammonia-lyase gene in Pichia pastoris - Zhang Jianhui; Wang Shoufeng (浙江大学学报. 农业与生命科学版, 2014)
L-phenylalanine, as an essential amino acid for human nutrition, is widely used in pharmaceutical and food industries. Using phenylalanine ammonia-lyase (PAL, EC 4.3.1.5) to produce L-phenylalanine is one of the major routes. However, most commercial enzymes are extracted from Rhodotorula glutinis, which is timeconsuming and over-priced. Therefore, how to efficiently construct the genetic engineering strain to produce PAL is the hot topic.Pichia pastoris is popular in expressing heterologous proteins due to the advantages of low nutritional demands, excellent genetic stability and high-density fermentation. Inserting the heterologous gene into pPIC9K vector to achieve secreted expression in P. pastoris has been reported. However, unlike other vectors, pPIC9K has few desirable restriction enzyme cutting sites, which reduces vector construction efficiency when the classical method of digestion and then ligation is adopted. Under this condition, an efficient cloning strategy, independent of digestion and ligation, is required. Homologous recombination in vitro between pPIC9K and gene can settle this problem. Now, we intend to employ homologous recombination in vitro cloning method to insert the PAL gene into pPIC9K vector to obtain secreted expression in P. pastoris in order to lay the basis for industrial fermentation.First, total RNA extracted from Astragalus membranaceus was used as template for isolating cDNA. Open reading frame (ORF) of PAL gene was amplified by PCR from cDNA with a pair of primers designed according to the sequence of PAL gene published in the GenBank. Then, ORF was cloned into vector pUCm-T. The transformant was selected to sequence for further analysis of the PAL gene sequence with the help of bioinformatics tools. After that, pPIC9K-PAL was constructed by homologous recombination in vitro. Similarly, the transformant was selected to sequence to investigate the base mutation caused by PCR. Linearized pPIC9K-PAL by SalⅠ was transformed into P. pastoris GS115 by electroporation. Positive strains were screened on MD and then YPD-G418 plates. The strain resistant to 2.0 mg/mL G418 was selected to express induced by 1% methanol every 24 hours. Supernatant was collected for expression analysis at 0, 12, 24, 48, 72, 96, 120 and 144 h. The recombined PAL protein was purified by Q sepharose fast flow chromatography. Finally, protein concentration was measured with Bradford method and enzyme activity was analysed by measuring the absorption of resultant transcinnamic acid at 290 nm.After PAL was subcloned into pUCm-T, the result of sequencing indicated that about 2 200 bp ORF sequence of PAL gene was cloned from A. membranaceus. With the help of bioinformatics methods, it was predicted that PAL encoded a protein which was about 78 ku in molecular mass and 6.04 in pI, containing 718 amino acid residues. Amino acid sequence alignment revealed that the PAL shared 99% identity with PAL from A. membranaceus published in the NCBI. After homologous recombination in vitro between pPIC9K and PAL, the two evidences that about 900 bp fragment which was coincident with the expectation was obtained from the recombinant plasmid pPIC9K-PAL by Eco RⅠ double digestion and that furthering analysis of sequencing both suggested that PAL was successfully constructed into pPIC9K without any mutation compared with the first sequencing. After linearized pPIC9K-PAL was transformed into P. pastoris GS115, colony PCR indicated PAL gene was integrated into the yeast chromosome in contrast to the negative control. The strain resistant to 2.0 mg/mL G418 was selected to express. SDS-PAGE demonstrated that a sharp 78 ku protein which was equal to the predicted value was expressed in the supernatant in contrast to the parent pPIC9K. By Q sepharose fast flow chromatography, the protein was well purified. The concentration of purified protein was 0.08 mg/mL, accounting for 11.54% of total proteins and the specific activity of GS115/pPIC9K-PAL-3 was 4 270 U/mg.This study supplies a novel cloning strategy to insert the target gene into pPIC9K vector by homologous recombination in vitro which makes vector construction get rid of the limitation of restriction enzyme cutting site. Meanwhile, the expression of PAL gene in P. pastoris GS115 has laid the foundation for using genetic engineering technology to produce PAL in large scale.